Serum levels of osteopontin are increased in SIRS and sepsis - Vaschetto, Rosanna; Nicola, Stefania; Olivieri, Carlo; Boggio, Elena; Piccolella, Fabio; Mesturini, Riccardo; Damnotti, Federica; Colombo, Davide; Navalesi, Paolo; Della Corte, Francesco; Dianzani, Umberto; Chiocchetti, Annalisa (Intensive care medicine, 2008)
Objective In sepsis, dysregulation of the immune response leads to rapid multiorgan failure and death. Accurate and timely diagnosis is lifesaving and should discriminate sepsis from the systemic inflammatory response syndrome (SIRS) caused by non-infectious agents. Osteopontin acts as an extracellular matrix component or a soluble cytokine in inflamed tissues. Its exact role in immune response and sepsis remains to be elucidated. Therefore, we investigated the role of osteopontin in SIRS and sepsis. Design Prospective, observational study. Setting Intensive care unit of a university hospital. Patients and participants Fifty-six patients with SIRS or sepsis and 56 healthy subjects were enrolled. Interventions We analyzed the serum levels of osteopontin and TH1–TH2 cytokines and investigated the role of osteopontin on interleukin 6 secretion by monocytes. Measurements and main results Serum osteopontin levels were strikingly higher in patients than in controls and in sepsis than in SIRS, and decreased during the resolution of both the disorders. Receiver operating characteristic curves showed that osteopontin levels have discriminative power between SIRS and sepsis with an area under the curve of 0.796. Osteopontin levels directly correlated with those of interleukin 6 and in vitro, recombinant osteopontin increased interleukin 6 secretion by monocytes in both the absence and presence of high doses of lipopolysaccharide. Conclusion These data suggest that osteopontin might be a mediator involved in the pathogenesis of SIRS and sepsis, possibly by supporting interleukin 6 secretion. Descriptor 45. SIRS/Sepsis: clinical studies.